Rapid Excavation and Tunneling Conference 2017 Proceedings. - Lawrence, Colin A. (Society for Mining Metallurgy and Exploration, 2017)
Annotation RETC: The largest and most prominent conference on a tunneler's calendarEvery two years, industry leaders and practitioners from around the world gather at the Rapid Excavation and Tunneling Conference (RETC), the authoritative program for the tunneling profession, to learn about the most recent advances and breakthroughs in this unique field.Tunnels are getting larger, deeper, and excavated in more challenging conditions. The expectation for the industry is to successfully complete these projects while meeting the other heavy construction challenges of sustaining quality, schedule, performance, and safety.This comprehensive proceedings will help you keep up with the ever-changing and growing tunneling industry. It includes the full text of 97 papers presented at the 2017 conference. Stay on top of new trends and technologies as well as innovative concepts, new equipment, materials, management, financing, and design challenges.
Keywords: Tunneling -- Congresses.; Excavation -- Congresses.; Underground construction -- Congresses.; elektronické knihy; electronic books